2016
DOI: 10.1002/j.0022-0337.2016.80.3.tb06093.x
|View full text |Cite
|
Sign up to set email alerts
|

Profile of Department Chairs in U.S. and Canadian Dental Schools: Demographics, Requirements for Success, and Professional Development Needs

Abstract: The aim of this survey study was to develop a current profile of department chairs at U.S. and Canadian dental schools. The survey asked respondents to identify their responsibilities; describe the competencies needed to best serve in the position; and assess their needs in terms of professional development. An online survey with 35 items was sent to 754 individuals who self-identified as department chairs, department heads, or program directors. Overall, 269 responses were received (overall response rate of 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 28 publications
(39 reference statements)
1
19
0
1
Order By: Relevance
“…This possibility is highlighted by how little emphasis was placed on budgeting and financing by department chairpersons in Wee et al's study, but it factored heavily in the deans' own perceptions of what department chairpersons need to be successful, in both Brundo and O'Brien's study and ours. Rodriguez et al reported that less than half of department chairpersons were responsible for managing the budget of their own department, with only a small fraction of those having a financial manager for the department 10 . This finding may suggest that many financial duties are the responsibility of the dean and other administrative staff, but those financial arrangements will differ based on the budgeting model of each university and will vary over time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This possibility is highlighted by how little emphasis was placed on budgeting and financing by department chairpersons in Wee et al's study, but it factored heavily in the deans' own perceptions of what department chairpersons need to be successful, in both Brundo and O'Brien's study and ours. Rodriguez et al reported that less than half of department chairpersons were responsible for managing the budget of their own department, with only a small fraction of those having a financial manager for the department 10 . This finding may suggest that many financial duties are the responsibility of the dean and other administrative staff, but those financial arrangements will differ based on the budgeting model of each university and will vary over time.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, department chairpersons reported feeling that leadership skills were more critical to success in their position than management skills 9, 10 . In one of those studies, restorative department chairpersons perceived that the six most essential characteristics to their success were leadership, vision, work ethic, integrity, communication, and organization 9 .…”
mentioning
confidence: 99%
“…Their role has been evolving in response to the varying landscape of health care reform, new technology, and advancement of knowledge in the field of medical education (3). To succeed in this environment, it is critical that department chair roles are continuing to develop for efficiency of department functions (4).Additionally, the requirement to provide a realistic and comprehensive system for performance improvement of academic department chair cause a rising need for adaptation strategies that should be implemented in higher education system (5). Based on the results of the study of Lieff et al (2013), access to a comprehensive network of support and guidance was the most important factor influencing the performance of department chairs (2).…”
Section: Introductionmentioning
confidence: 99%
“…Although some of them are acquired during the work experience, the others are harder to learn in comparison to the others 11,12. Improvement of managerial competencies will be done through appropriate training in a systematic framework 13…”
Section: Introductionmentioning
confidence: 99%